Upconverting nanoparticles for the near infrared photoactivation of transition metal complexes: new opportunities and challenges in medicinal inorganic photochemistry - Ruggiero, Emmanuel; Alonso-de Castro, Silvia; Habtemariam, Abraha; Salassa, Luca (Dalton transactions : an international journal of inorganic chemistry, 2016)
The article highlights the emergent use of upconverting nanoparticles as tools for the near infrared photoactivation of transition metal complexes, identifying opportunities and challenges of this approach in the context of medicinal inorganic chemistry. The article highlights the emergent use of upconverting nanoparticles as tools for the near infrared photoactivation of transition metal complexes.